14
$\begingroup$

For sequence $u_n$ satisfing : $$\begin{cases} u_1=\sqrt{2015}\\ u_{n+1}=u_n^2-2\end{cases}$$ How to prove : $$\lim_{n\to+\infty}\left(\dfrac{u_{n+1}}{u_1.u_2...u_n}\right)^2=2011$$

$\endgroup$
  • $\begingroup$ The Maple command $$rsolve(\{u(1) = 2015^{1/2}, u(n+1) = u(n)^2-2\}, u) $$ produces $$2\,\cosh \left( 1/2\,{\it arccosh} \left( 1/2\,\sqrt {2015} \right) {2 }^{n} \right). $$ $\endgroup$ – user64494 Sep 2 '13 at 7:43
  • $\begingroup$ After simplification with Maple $$ \left( e^{\ln \left( 1/2\,\sqrt {2015}+1/4\,\sqrt {-4+2\, \sqrt {2015}}\sqrt {4+2\,\sqrt {2015}} \right) 2^n}+1 \right)* $$ $$ e^{-1/2\,\ln \left( 1/2\,\sqrt {2015}+1/4\,\sqrt {-4+2\,\sqrt {2015}}\sqrt {4+2\,\sqrt {2015}} \right) 2^n} $$ $\endgroup$ – user64494 Sep 2 '13 at 8:13
  • $\begingroup$ I'm surprised 'Maple' didn't do the further simplification that $e^{-1/2\ln(??)}=1/\sqrt{??}$. And I wouldn't say that an expression of the form $e^{\ln(\dots)}$ is completely simplified.... $\endgroup$ – John Gowers Sep 2 '13 at 14:10
  • 1
    $\begingroup$ Simplifying Maple's simplification in a few naive ways gives $u_n=\sqrt{2^n\left(\frac12\sqrt{2015}+\frac14\sqrt{2011}\right)}+\dfrac1 {\sqrt{2^n\left(\frac12\sqrt{2015}+ \frac14 \sqrt{2011}\right)}}$ (I wouldn't be surprised if you could simplify this further). $\endgroup$ – John Gowers Sep 2 '13 at 14:26
22
$\begingroup$

The recurrence relation may be expressed as $$ {u_{n}}^2 = \frac{{u_{n+1}}^2 - 4}{{u_{n}}^2 - 4}. $$

Which allows telescopic cancellation,

$$ \begin{align*} \left ({u_{1}}{u_{2}}\cdots{u_{n}}\right )^2 &= \left (\frac{\color{#036}{{u_{2}}^{2} - 4}}{{u_{1}}^2 - 4} \right ) \left ( \frac{\color{#063}{{u_{3}}^{2} - 4}}{\color{#036}{{u_{2}}^2 - 4}} \right ) \cdots \left ( \frac{{u_{n+1}}^{2} - 4}{\color{#630}{{u_{n}}^2 - 4}} \right )\\[10pt] &= \frac{{u_{n+1}}^2 - 4}{{u_{1}}^2 - 4}. \end{align*} $$

Hence,

$$ \begin{align*} \lim_{n\to\infty} \left ( \frac{u_{n+1}}{{u_{1}}{u_{2}}\cdots{u_{n}}} \right )^2 &= \lim_{n\to\infty} {u_{n+1}}^2 \cdot \frac{{u_{1}}^2 - 4}{{u_{n+1}}^2 - 4}\\ &= \lim_{n\to\infty} \left ( {u_{1}}^2 - 4\right ) \cdot \frac{1}{1 - 4/{u_{n+1}}^2}\\ &= {u_{1}}^2 - 4 &\text{since $\lim_{n\to\infty} 1/u_{n+1} = 0$}. \end{align*} $$

Substituting $u_1 = \sqrt{2015}$ yields the final result

$$\lim_{n\to\infty} \left ( \frac{u_{n+1}}{{u_{1}}{u_{2}}\cdots{u_{n}}} \right )^2 = 2011.$$

$\endgroup$
5
$\begingroup$

Here I use its properties as an additive telescoping series: $$\left(\frac{u_n^2-2}{u_1\cdots u_n}\right)^2=\frac{u_n^4}{(u_1\cdots u_n)^2}-\frac{4u_n^2}{(u_1\cdots u_n)^2}+\frac{4}{(u_1\cdots u_n)^2}$$ $$=\frac{u_n^2}{(u_1\cdots u_{n-1})^2}-\frac{4}{(u_1\cdots u_{n-1})^2}+\frac{4}{(u_1\cdots u_n)^2}$$ Substitute again: $$=\left(\frac{u_{n-1}^2}{(u_1\cdots u_{n-2})^2}-\frac{4}{(u_1\cdots u_{n-2})^2}+\frac{4}{(u_1\cdots u_{n-1})^2} \right)-\frac{4}{(u_1\cdots u_{n-1})^2}+\frac{4}{(u_1\cdots u_n)^2}$$ $$=\frac{u_{n-1}^2}{(u_1\cdots u_{n-2})^2}-\frac{4}{(u_1\cdots u_{n-2})^2}+\frac{4}{(u_1\cdots u_n)^2}$$ And again: $$=\left(\frac{u_{n-2}^2}{(u_1\cdots u_{n-3})^2}-\frac{4}{(u_1\cdots u_{n-3})^2}+\frac{4}{(u_1\cdots u_{n-2})^2} \right)-\frac{4}{(u_1\cdots u_{n-2})^2}+\frac{4}{(u_1\cdots u_n)^2}$$

$$=\frac{u_{n-2}^2}{(u_1\cdots u_{n-3})^2}-\frac{4}{(u_1\cdots u_{n-3})^2}+\frac{4}{(u_1\cdots u_n)^2}$$

Reapeat this process ad infinitum (noting that $\lim_{n \rightarrow \infty}u_n= \infty$):

$$=\frac{u_{2}^2}{(u_1)^2}-\frac{4}{(u_1)^2}+\frac{4}{(u_1\cdots u_n)^2}$$

And take the limit $n \rightarrow \infty$:

$$=\frac{(2015-2)^2}{2015}-\frac{4}{2015}+0$$ $$=\frac{2015^2-4\cdot 2015 +4}{2015}-\frac{4}{2015}$$ $$=2015-4=2011$$

$\endgroup$
3
$\begingroup$

\begin{aligned} u_{n+1} = {u_{n}}^2 - 2 \\ {u_{n+1}}^2 = ({u_{n}}^2 - 2)^2 \\ {u_{n+1}}^2 = {u_{n}}^4 - 4{u_{n}}^2 + 4 \\ {u_{n+1}}^2 - 4 = {u_{n}}^2({u_{n}}^2 - 4) \\ {u_{n}}^2 = \frac{{u_{n+1}}^2 - 4}{{u_{n}}^2 - 4} \end{aligned}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.